Perioperative outcomes in patients undergoing robot‐assisted partial nephrectomy: Comparative assessments between complex and non‐complex renal tumors. Issue 3 (1st October 2020) - Motoyama, Daisuke; Sato, Ryo; Watanabe, Kyohei; Matsushita, Yuto; Watanabe, Hiromitsu; Matsumoto, Rikiya; Ito, Toshiki; Sugiyama, Takayuki; Otsuka, Atsushi; Miyake, Hideaki
Abstract: Introduction: The aim of this study was to investigate the effects of renal tumor complexity on perioperative outcomes in patients receiving robot‐assisted partial nephrectomy (RAPN). Methods: This study included 153 consecutive patients with cT1 renal masses undergoing RAPN and analyzed their perioperative outcomes, particularly tumor complexity. In this series, cT1b, completely endophytic, hilar, and cystic tumors were considered complex tumors. Patients with tumors that met at least one of the complex criterion were placed in the complex tumor group; patients with tumors that did not meet any of the complex criteria were placed in the non‐complex tumor group. Results: Of the 153 patients, 54 (35.3%) had complex tumors; specifically, 18 (11.8%) had cT1b tumors, 15 (9.8%) had completely endophytic tumors, 28 (18.3%) had hilar tumors, and 8 (5.2%) had cystic tumors. The non‐complex group included 99 patients (64.7%). The complex tumor group had significantly longer warm ischemia and console times than the non‐complex tumor group, but there was no significant difference between them in the achievement of the trifecta. Both warm ischemia and console times were significantly correlated with the number of complex factors. Multivariate analyses of complex factors demonstrated that completely endophytic and cT1b tumors were independently associated with warm ischemia time and console time, respectively. Conclusions: For patients with complex tumors, RAPN may be a feasible procedure with acceptable perioperative outcomes. However, special attention should be paid to long warm ischemia and console times, particularly in those with completely endophytic and/or cT1b tumors.